Infant and early childhood mental health consultation in a diverse metropolitan area. Issue 3 (25th May 2022) - Natale, Ruby; Kolomeyer, Ellen; Futterer, Jenna; Mahmoud, Farah D.; Schenker, Maite; Robleto, Ana; Horen, Neal; Spector, Rachel
Abstract: IECMHC can and should be a vehicle that promotes greater equity in access to high quality relationships within an early classroom environment. It is important to consider consultation through a racial equity lens to ensure that it is integrated in all levels of work. The goal of the study was to replicate the results from other IECMHC programs with a diverse, largely Latinx, population. The Jump Start program was given the unique opportunity to adapt the Georgetown Framework of Infant and Early Childhood Mental Health Consultation to a multicultural population in Miami. A total of 88 early learning programs and 244 teachers participated. Services were provided in English, Spanish, and Creole at the program‐ and classroom‐level. Pre‐ and post‐data were collected at both levels. Significant improvements at the program‐ and classroom‐level were found post‐consultation. Consultants demonstrated fidelity to core program practices while providing culturally and linguistically competent service. The current study replicated findings regarding the effectiveness of IECMHC while expanding results to a diverse metropolitan community. Key features of program success may be attributed to the use of highly trained consultants, action planning, fidelity monitoring, and enrollment of programs that were ready and have a champion for IECMHC. Resumen: Trasfondo: la Consulta de Salud Mental en la Infancia y Temprana Niñez (IECMHC) puede y deber ser un medio para promover mayor equidad en cuanto al acceso a relaciones de alta calidad dentro del ambiente de la temprana aula de clases. Es importante considerar la consulta a través de un lente de equidad racial para asegurar que la misma se integra en todos los niveles de trabajo. El propósito de este estudio fue replicar los resultados de otros programas de IECMHC con una población diversa, mayoritariamente Latinx. Método: el programa Jump Start (de Buen Comienzo) tuvo la oportunidad única de adaptar el Marco de Trabajo de Georgetown para la Consulta de Salud Mental en la Infancia y Temprana Niñez a un grupo de población multicultural en Miami. Participaron ochenta y ocho programas de aprendizaje temprano y 244 maestros. Se ofrecieron los servicios en inglés, español y creole a niveles de programa y de aula de clases. En ambos niveles se recogió información previa y posterior. Resultados: se dieron significativas mejoras posteriores a la consulta al nivel de programa y de aula de clases. Los consultantes demostraron fidelidad a las prácticas centrales del programa mientras que ofrecían un servicio competente cultural y lingüísticamente. Conclusiones: el presente estudio replicó los resultados acerca de la eficacia de IECMHC al tiempo que los expandía a una comunidad metropolitana diversa. Las características claves del éxito del programa pueden ser atribuidas al empleo de consultantes altamente entrenados, plan de acción, fiel supervisión y la participación de programas que estaban listos y cuentan con defensores de IECMHC. Résumé: Contexte: L'IECMHC doit et devrait être un véhicule qui promeut une plus grande équité dans l'accès à des relations de haute qualité au sein de l'environnement en milieu scolaire. Il est important de considérer la consultation au travers du prisme de l'équité raciale pour s'assurer qu'elle était intégrée aux niveaux du travail. Le but de cette étude était de répliquer les résultats d'autres programmes IECMHC avec une population diverse, Latinx. Méthode: Le programme Jump Start a eu l'occasion d'adapter la Structure de Georgetown de la Consultation de Santé Mentale du Nourrisson et de la Petite Enfance à une population multiculturelle de Miami en Floride. 88 programmes d'apprentissage précoce et 244 enseignants ont participé. Des services ont été offerts en anglais, en espagnol et en créole au niveau du programme et de la salle de classe à la crèche. Des données avant et après ont été relevées aux deux niveaux. Résultats: Des améliorations importantes au niveau du programme et au niveau de la salle de classe ont été trouvées après la consultation. Les consultants ont fait preuve de fidélité aux pratiques du programme principal tout en offrant un service culturellement et linguistiquement compétent. Conclusions: Cette étude a répliqué les résultats concernant l'efficacité de l'IECMHC tout en élargissant les résultats à une communauté métropolitaine diverse. Les aspects clé du succès du programme peuvent être attribués à l'utilisation de consultant très formés, aux plans d'action, à la fidélité du suivi et aux inscriptions dans des programmes qui étaient prêts et avaient en leur sein un avocat de l'IECMHC. Zusammenfassung: Beratung zur psychischen Gesundheit von Säuglingen und Kleinkindern in einem heterogenen Großstadtgebiet Hintergrund: IECMHC (Infant and Early Childhood Mental Health Consultation) kann und sollte ein Instrument sein, das einen gerechteren Zugang zu qualitativ hochwertigen Beziehungen im Kontext der Früherziehung fördert. Es ist wichtig, die Beratung unter dem Aspekt der Gleichstellung zwischen Menschen verschiedener Ethnien zu betrachten, um sicherzustellen, dass sie in alle Arbeitsebenen integriert wird. Das Ziel dieser Studie war es, die Ergebnisse anderer IECMHC‐Programme innerhalb einer diversen, überwiegend lateinamerikanischen Population zu replizieren. Methode: Das „Starthilfeprogramm" erhielt die einmalige Gelegenheit, das „Georgetown Framework of Infant and Early Childhood Mental Health Consultation" an eine multikulturelle Bevölkerung in Miami anzupassen. 88 Frühförderprogramme und 244 Lehrkräfte nahmen teil. Die Intervention wurde in Englisch, Spanisch und Kreolisch entweder als eigenes Programm oder im Rahmen des Schulunterrichts angeboten. In beiden Fällen wurden Prä‐ und Postdaten erhoben. Ergebnisse: Nach der Beratung wurden innerhalb der Programme und im Schulunterricht signifikante Verbesserungen festgestellt. Die Beratenden hielten sich an die wichtigsten Programmpraktiken und boten gleichzeitig kulturell und sprachlich kompetente Leistungen an. Schlussfolgerungen: Die vorliegende Studie war in der Lage, Wirksamkeitsergebnisse von IECMHC zu replizieren und auf ein diverses Großstadtgebiet auszuweiten. Der Erfolg des Programms kann im Wesentlichen auf den Einsatz hochqualifizierter Beratender, auf die Aktionsplanung und auf das Monitoring der Programmtreue zurückgeführt werden. Außerdem war es wichtig, dass die IECMHC in Programme integriert wurde, die eine Bereitschaft für das Konzept zeigten und eine dafür verantwortliche Person bestimmten. 抄録: タイトル 多様性のある大都市地区における乳幼児精神保健相談 (Infant and Early Childhood Mental Health Consultation:IECMHC) 背景: IECMHCは、早期の教室環境における質の高い関係性につながる、より公平性の高い手段となり得るし、またそうあるべきである。人種的平等のレンズを通して相談について考慮し、それがすべてのレベルの作業で統合されているという保証が重要である。本研究の目的は、多様な、主にラテンアメリカ系集団を対象とした他のIECMHCプログラムから結果を再現することであった。 方法:ジャンプ・スタート・プログラムは、ジョージタウン方式IECMHCを、マイアミの多文化な住民に適応させるというユニークな機会を得た。88 の早期学習プログラムと 244 人の教師が参加した。プログラムでも教室レベルでも、英語、スペイン語、クレオール語で実施された。両レベルで事前と事後のデータが収集された。 結果:相談後、プログラムおよび教室レベルで有意な改善が見られた。コンサルタントは、文化的・言語的にも適切なサービスを提供しながら、中核的プログラムの実践に忠実であると示された。 結論 :本研究は、IECMHCの有効性に関する報告を再現すると同時に、多様な大都市コミュニティに結果を発展させた。プログラムの成功の鍵は, 高度に訓練されたコンサルタントの活用、行動計画, 忠実度の監視, そしてプログラムへの登録、それらがIECMHCの為に準備され、そして強力な擁護者がいたことにあると考えられる。 摘要: 研究背景:为在早期课堂环境中建立高质量的人际关系, IECMHC可以而且应该成为促进更大公平的工具。重要的是要考虑通过种族平等的视角开展咨询, 以确保将其纳入各级工作中。该研究的目的是利用不同人群 (主要是拉丁裔) 复现其他IECMHC计划的研究结果。 研究方法:"跳跃启动"计划获得了难得的机会, 以使乔治城"婴幼儿心理健康咨询框架"适应迈阿密的多元文化人群。88个早期学习课程和244名教师参加了这一计划。在课程学习和课堂层面, 以英语、西班牙语和克里奥尔语提供服务, 并在这两个层面上收集了前期和后期数据。 研究结果:咨询后发现, 课程学习和课堂水平有了显著改善。咨询顾问在提供文化和语言上称职服务的同时, 确保了核心计划实践的保真度。 研究结论:当前的研究复现了关于IECMHC有效性的研究发现, 同时将研究结果扩展到了多元的大都市社区。计划成功的关键要素可能归因于使用了训练有素的顾问、行动规划、保真度监控, 以及已准备好并拥有IECMHC计划支持者的注册课程。 ملخص: استشارات الصحة النفسية للرضع والأطفال في مرحلة الطفولة المبكرة في منطقة حضرية متنوعة الخلفية: يمكن وينبغي أن تكون استشارات الصحة النفسية وسيلة لتعزيز قدر أكبر من المساواة في الوصول إلى علاقات عالية الجودة داخل بيئة الفصل الدراسي المبكر. من المهم تناول الاستشارة من منظور العدالة العرقية لضمان دمجها في جميع مستويات العمل. كان الهدف من الدراسة هو إعادة النتائج من برامج الاستشارات الصحة النفسية الأخرى مع مجموعة متنوعة بشكل أكبر من السكان اللاتينيين. الطريقة: تم منح برنامجJump Start فرصة فريدة لتطويع إطار عمل جورجتاون لاستشارات الصحة النفسية للرضع والأطفال في مرحلة الطفولة المبكرة مع السكان متعددي الثقافات في ميامي. شارك 88 برنامج تعليم مبكر و 442 معلمًا في هذه الدراسة. تم تقديم الخدمات باللغات الإنجليزية والإسبانية والكريولية على مستوى البرنامج والفصل الدراسي. وتم جمع البيانات السابقة واللاحقة على كلا المستويين. النتائج: وجدت تحسنات كبيرة على مستوى البرنامج والفصول الدراسية بعد الاستشارات. أظهر الاستشاريون الإخلاص لممارسات البرنامج الأساسية مع تقديم خدمة مختصة ثقافيًا ولغويًا. الاستنتاجات: الدراسة الحالية أعادت تطبيق النتائج المتعلقة بفعالية استشارات الصحة النفسية للرضع والأطفال مع توسيع النتائج إلى مجتمع حضري متنوع. يمكن أن تُعزى السمات الرئيسية لنجاح البرنامج إلى استخدام مستشارين مدربين تدريباً عالياً ، وتخطيط العمل ، ومراقبة الأمانة ، والتسجيل في البرامج التي كانت جاهزة ومهيئة لاستشارات الصحة النفسية.